A Prototype Audio-Tactile Map System with an Advanced Auditory Display - O'Sullivan, Liam; Picinali, Lorenzo; Gerino, Andrea; Cawthorne, Douglas (International journal of mobile human computer interaction, 2015)
Tactile surfaces can display information in a variety of applications for all users, but can be of particular benefit to blind and visually impaired individuals. One example is the use of paper-based tactile maps as navigational aids for interior and exterior spaces; visually impaired individuals may use these to practice and learn a route prior to journeying. The addition of an interactive auditory display can enhance such interfaces by providing additional information. This article presents a prototype system which tracks the actions of a user's hands over a tactile surface and responds with sonic feedback. The initial application is an Audio-Tactile Map (ATM); the auditory display provides verbalised information as well as environmental sounds useful for navigation. Two versions of the interface are presented; a desktop version intended as a large-format information point and a mobile version which uses a tablet computer overlain with tactile paper. Details of these implementations are provided, including observations drawn from the participation of a partially-sighted individual in the design process. A usability test with five visually impaired subjects also gives a favourable assessment of the mobile version.